Peace Education in Conflict Area of Prince of Songkla University, Pattani Campus - Panjor, Fareeda; Sattar, Yasmin (Journal of Human Rights and Peace Studies, 2021)
This research article on Peace Education in Conflict Area of Prince of Songkla University, Pattani Campusaims to study the development on teaching peace and the student’ s reflection that are related to the subject 117-114 Living a Peaceful Life course through the concept of Peace Education. The study is done through mixed methodologies—both quantitative and qualitative which is the study on the content and purposes of Living aPeaceful Life’s course that let the students understand the ideas of self- consciousness and understand others, positive worldviews, concept ofidentity, open- minded to coexistence in cultural diversity, peace and non-violence, conflict analysis, peace communication and peace process in the Deep South of Thailand.Moreover, the study on the perception of youth and teachers,most of students think that there are some positively changes in perceptions and idea toward other people in society. However, some challenges from perspectives of peace education have been found on the need of understanding on people’ s identity profoundly in the Thailand’ s Deep South conflict. Also, there is a limitation especially on the large number of students in class, the continuity of diverse contents in one course and the need of student to learning from community effected from violence.